Role of Fatty Acids/Fat Soluble Component from Medicinal Plants Targeting BACE Modulation and Their Role in Onset of AD: An in-silico Approach - Anthwal, Prashant; Sati, Bipin Kumar; Thapliyal, Madhu; Verma, Devvret; Kumar, Navin; Thapliyal, Ashish (Journal of Graphic Era University, 2023)
<span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*354.77px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.902389);" role="presentation">Fatty acids have been <span dir="ltr" style="left: calc(var(–scale-factor)*163.10px); top: calc(var(–scale-factor)*354.77px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.899111);" role="presentation">reported <span dir="ltr" style="left: calc(var(–scale-factor)*199.73px); top: calc(var(–scale-factor)*354.77px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.914227);" role="presentation">in several <span dir="ltr" style="left: calc(var(–scale-factor)*241.85px); top: calc(var(–scale-factor)*354.77px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.882714);" role="presentation">researches targeting <span dir="ltr" style="left: calc(var(–scale-factor)*325.15px); top: calc(var(–scale-factor)*354.77px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.919578);" role="presentation">cure and treatment of Alzheimer’s disease <span dir="ltr" style="left: calc(var(–scale-factor)*499.78px); top: calc(var(–scale-factor)*354.77px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.0286);" role="presentation">(AD). <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*367.97px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.922897);" role="presentation">Besides having so many contradictory reports about fatty acids related to the issues of human health, there are <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*381.17px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.901769);" role="presentation">many evidences <span dir="ltr" style="left: calc(var(–scale-factor)*140.42px); top: calc(var(–scale-factor)*381.17px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.939513);" role="presentation">that point towards <span dir="ltr" style="left: calc(var(–scale-factor)*217.85px); top: calc(var(–scale-factor)*381.17px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.941236);" role="presentation">the beneficial effects of PUFAs and essential fatty acids on human health, <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*394.37px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.942665);" role="presentation">even in <span dir="ltr" style="left: calc(var(–scale-factor)*105.98px); top: calc(var(–scale-factor)*394.37px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.0098);" role="presentation">AD. <span dir="ltr" style="left: calc(var(–scale-factor)*126.50px); top: calc(var(–scale-factor)*394.37px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.949919);" role="presentation">This study <span dir="ltr" style="left: calc(var(–scale-factor)*173.18px); top: calc(var(–scale-factor)*394.37px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.908181);" role="presentation">inves<span dir="ltr" style="left: calc(var(–scale-factor)*194.45px); top: calc(var(–scale-factor)*394.37px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.956953);" role="presentation">tigated the interaction of fatty acids and phyto-<span dir="ltr" style="left: calc(var(–scale-factor)*389.83px); top: calc(var(–scale-factor)*394.37px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.971851);" role="presentation">constituents for the inhibition of <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*407.59px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.952589);" role="presentation">BACE enzyme (mainly responsible and prominent target for amyloid hypothesis) through <span dir="ltr" style="left: calc(var(–scale-factor)*447.70px); top: calc(var(–scale-factor)*407.59px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.99871);" role="presentation">in-<span dir="ltr" style="left: calc(var(–scale-factor)*458.86px); top: calc(var(–scale-factor)*407.59px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.973947);" role="presentation">silico <span dir="ltr" style="left: calc(var(–scale-factor)*484.18px); top: calc(var(–scale-factor)*407.59px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.883835);" role="presentation">approach. P<span dir="ltr" style="left: calc(var(–scale-factor)*77.66px); top: calc(var(–scale-factor)*420.91px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.933585);" role="presentation">hyto-<span dir="ltr" style="left: calc(var(–scale-factor)*98.54px); top: calc(var(–scale-factor)*420.91px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.89698);" role="presentation">compounds <span dir="ltr" style="left: calc(var(–scale-factor)*147.74px); top: calc(var(–scale-factor)*420.91px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.977509);" role="presentation">from P<span dir="ltr" style="left: calc(var(–scale-factor)*176.18px); top: calc(var(–scale-factor)*420.91px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.973773);" role="presentation">icrorhiza <span dir="ltr" style="left: calc(var(–scale-factor)*215.93px); top: calc(var(–scale-factor)*420.91px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.929638);" role="presentation">kurroa, Cinnamomum tamala, Curcuma <span dir="ltr" style="left: calc(var(–scale-factor)*381.31px); top: calc(var(–scale-factor)*420.91px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.919409);" role="presentation">longa, Datura metel, Rheum emodi <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*434.11px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.86296);" role="presentation">and <span dir="ltr" style="left: calc(var(–scale-factor)*89.06px); top: calc(var(–scale-factor)*434.11px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.928712);" role="presentation">Bacopa monnieri<span dir="ltr" style="left: calc(var(–scale-factor)*158.54px); top: calc(var(–scale-factor)*434.11px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.940764);" role="presentation">, which are well known, <span dir="ltr" style="left: calc(var(–scale-factor)*257.93px); top: calc(var(–scale-factor)*434.11px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.872725);" role="presentation">were screened. <span dir="ltr" style="left: calc(var(–scale-factor)*320.11px); top: calc(var(–scale-factor)*434.11px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.911209);" role="presentation">For screening of drug molecules, <span dir="ltr" style="left: calc(var(–scale-factor)*455.26px); top: calc(var(–scale-factor)*434.11px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.0002);" role="presentation">Lipinski<span dir="ltr" style="left: calc(var(–scale-factor)*488.62px); top: calc(var(–scale-factor)*434.11px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.0149);" role="presentation">’s <span dir="ltr" style="left: calc(var(–scale-factor)*498.34px); top: calc(var(–scale-factor)*434.11px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.939396);" role="presentation">rule is <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*447.31px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.905034);" role="presentation">usually used. <span dir="ltr" style="left: calc(var(–scale-factor)*127.70px); top: calc(var(–scale-factor)*447.31px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.921889);" role="presentation">Because of this rule <span dir="ltr" style="left: calc(var(–scale-factor)*211.49px); top: calc(var(–scale-factor)*447.31px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.894466);" role="presentation">compounds <span dir="ltr" style="left: calc(var(–scale-factor)*260.69px); top: calc(var(–scale-factor)*447.31px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.994667);" role="presentation">like <span dir="ltr" style="left: calc(var(–scale-factor)*278.69px); top: calc(var(–scale-factor)*447.31px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.922771);" role="presentation">Bacoside A, Bacoside A3, Bacopaside II, Bacopasaponin C, <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*460.51px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00289);" role="presentation">Baimantuoluoline C, Daturameteline A, Cucurbitacin B, Cucurbitacin D, Cucurbitacin E, Cucurbitacin I, <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*473.71px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.930332);" role="presentation">Cucurbitacin <span dir="ltr" style="left: calc(var(–scale-factor)*131.61px); top: calc(var(–scale-factor)*473.71px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.03584);" role="presentation">F, <span dir="ltr" style="left: calc(var(–scale-factor)*147.81px); top: calc(var(–scale-factor)*473.71px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.932491);" role="presentation">Cucurbitacin <span dir="ltr" style="left: calc(var(–scale-factor)*207.52px); top: calc(var(–scale-factor)*473.71px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.913);" role="presentation">R, <span dir="ltr" style="left: calc(var(–scale-factor)*224.66px); top: calc(var(–scale-factor)*473.71px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.909677);" role="presentation">Picroside <span dir="ltr" style="left: calc(var(–scale-factor)*269.97px); top: calc(var(–scale-factor)*473.71px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.13084);" role="presentation">III, <span dir="ltr" style="left: calc(var(–scale-factor)*290.55px); top: calc(var(–scale-factor)*473.71px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.935182);" role="presentation">Kutkoside, <span dir="ltr" style="left: calc(var(–scale-factor)*342.11px); top: calc(var(–scale-factor)*473.71px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.909677);" role="presentation">Picroside <span dir="ltr" style="left: calc(var(–scale-factor)*387.42px); top: calc(var(–scale-factor)*473.71px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.20275);" role="presentation">II <span dir="ltr" style="left: calc(var(–scale-factor)*402.14px); top: calc(var(–scale-factor)*473.71px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.847983);" role="presentation">are <span dir="ltr" style="left: calc(var(–scale-factor)*422.83px); top: calc(var(–scale-factor)*473.71px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.933991);" role="presentation">usually <span dir="ltr" style="left: calc(var(–scale-factor)*459.70px); top: calc(var(–scale-factor)*473.71px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.906318);" role="presentation">excluded <span dir="ltr" style="left: calc(var(–scale-factor)*503.93px); top: calc(var(–scale-factor)*473.71px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.977509);" role="presentation">from <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*487.03px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.933383);" role="presentation">docking/binding studies <span dir="ltr" style="left: calc(var(–scale-factor)*172.34px); top: calc(var(–scale-factor)*487.03px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.894438);" role="presentation">because of <span dir="ltr" style="left: calc(var(–scale-factor)*219.53px); top: calc(var(–scale-factor)*487.03px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.944093);" role="presentation">their <span dir="ltr" style="left: calc(var(–scale-factor)*241.49px); top: calc(var(–scale-factor)*487.03px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.947147);" role="presentation">higher molecular weight <span dir="ltr" style="left: calc(var(–scale-factor)*344.83px); top: calc(var(–scale-factor)*487.03px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.977594);" role="presentation">as they do now follow <span dir="ltr" style="left: calc(var(–scale-factor)*441.58px); top: calc(var(–scale-factor)*487.03px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.984007);" role="presentation">the Lipinski<span dir="ltr" style="left: calc(var(–scale-factor)*490.78px); top: calc(var(–scale-factor)*487.03px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.0149);" role="presentation">’s <span dir="ltr" style="left: calc(var(–scale-factor)*501.46px); top: calc(var(–scale-factor)*487.03px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.899507);" role="presentation">rules. <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*500.23px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.901347);" role="presentation">The same applies to fatty acids, <span dir="ltr" style="left: calc(var(–scale-factor)*201.05px); top: calc(var(–scale-factor)*500.23px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.994667);" role="presentation">like <span dir="ltr" style="left: calc(var(–scale-factor)*218.57px); top: calc(var(–scale-factor)*500.23px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.97696);" role="presentation">Linolinic acid. O<span dir="ltr" style="left: calc(var(–scale-factor)*286.73px); top: calc(var(–scale-factor)*500.23px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.897509);" role="presentation">n the basis of <span dir="ltr" style="left: calc(var(–scale-factor)*342.55px); top: calc(var(–scale-factor)*500.23px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.99871);" role="presentation">in-<span dir="ltr" style="left: calc(var(–scale-factor)*353.71px); top: calc(var(–scale-factor)*500.23px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.973947);" role="presentation">silico <span dir="ltr" style="left: calc(var(–scale-factor)*377.95px); top: calc(var(–scale-factor)*500.23px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.897326);" role="presentation">experiments, <span dir="ltr" style="left: calc(var(–scale-factor)*431.83px); top: calc(var(–scale-factor)*500.23px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.91701);" role="presentation">our study <span dir="ltr" style="left: calc(var(–scale-factor)*471.94px); top: calc(var(–scale-factor)*500.23px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.868265);" role="presentation">suggests that <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*513.43px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.925768);" role="presentation">certain polyunsaturated fatty acids (PUFA) and some saturated fatty acids <span dir="ltr" style="left: calc(var(–scale-factor)*376.51px); top: calc(var(–scale-factor)*513.43px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.929917);" role="presentation">of medicinal plants can have <span dir="ltr" style="left: calc(var(–scale-factor)*496.78px); top: calc(var(–scale-factor)*513.43px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.981304);" role="presentation">BACE <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*526.63px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.997511);" role="presentation">inhibition activity <span dir="ltr" style="left: calc(var(–scale-factor)*147.98px); top: calc(var(–scale-factor)*526.63px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.949791);" role="presentation">and can possibly modulate Aβ formation. <span dir="ltr" style="left: calc(var(–scale-factor)*322.75px); top: calc(var(–scale-factor)*526.63px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.923006);" role="presentation">Our study also suggests that compounds that are <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*539.83px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.969742);" role="presentation">excluded by Lipinski<span dir="ltr" style="left: calc(var(–scale-factor)*158.66px); top: calc(var(–scale-factor)*539.83px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.0149);" role="presentation">’s <span dir="ltr" style="left: calc(var(–scale-factor)*169.34px); top: calc(var(–scale-factor)*539.83px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.990162);" role="presentation">rule/filter durin<span dir="ltr" style="left: calc(var(–scale-factor)*232.01px); top: calc(var(–scale-factor)*539.83px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.944595);" role="presentation">g bioinformatics based screening due to their molecular weight should <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*554.83px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.904256);" role="presentation">also be tested in experiments as we hypothesize that Lipinski<span dir="ltr" style="left: calc(var(–scale-factor)*316.27px); top: calc(var(–scale-factor)*554.83px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.0149);" role="presentation">’s <span dir="ltr" style="left: calc(var(–scale-factor)*325.87px); top: calc(var(–scale-factor)*554.83px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.905953);" role="presentation">rule is not absolute.